The Influence of Colour Preferences on Cost of Living Allocation - Natania, Lalu Muhammad Gian; Fikri, Muhammad Ali (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the psychological relationship between the preference for color by individuals and the allocation of costs spent. This research is important to understand the relationship between color and the allocation of costs made by a person. In allocating the income received, it can be divided into several expenditure items. This cost allocation can be psychologically linked to the favorite color which in this study found a relationship between individuals who like primary and neutral colors. The method used in this research is quantitative descriptive. The data analysis technique uses bivariate correlation analysis. The sample used was 110 respondents using questionnaire data collection techniques. The sample is accounting students who are taking accounting theory courses. The data analysis tool used is SPSS (Statistical Product and Service Solution) version 25.